A herbal medicine for Alzheimer's disease and its active constituents promote neural progenitor proliferation. Issue 5 (25th May 2015) - Mao, Jianxin; Huang, Shichao; Liu, Shangfeng; Feng, Xiao‐Lin; Yu, Miao; Liu, Junjun; Sun, Yi Eve; Chen, Guoliang; Yu, Yang; Zhao, Jian; Pei, Gang
Summary Aberrant neural progenitor cell (NPC) proliferation and self‐renewal have been linked to age‐related neurodegeneration and neurodegenerative disorders including Alzheimer's disease (AD). Rhizoma Acori tatarinowii is a traditional Chinese herbal medicine against cognitive decline. In this study, we found that the extract of Rhizoma Acori tatarinowii (AT) and its active constituents, asarones, promote NPC proliferation. Oral administration of AT enhanced NPC proliferation and neurogenesis in the hippocampi of adult and aged mice as well as that of transgenic AD model mice. AT and its fractions also enhanced the proliferation of NPCs cultured in vitro. Further analysis identified α‐asarone and β‐asarone as the two active constituents of AT in promoting neurogenesis. Our mechanistic study revealed that AT and asarones activated extracellular signal‐regulated kinase (ERK) but not Akt, two critical kinase cascades for neurogenesis. Consistently, the inhibition of ERK activities effectively blocked the enhancement of NPC proliferation by AT or asarones. Our findings suggest that AT and asarones, which can be orally administrated, could serve as preventive and regenerative therapeutic agents to promote neurogenesis against age‐related neurodegeneration and neurodegenerative disorders.